2003
DOI: 10.1046/j.1525-142x.2003.03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evolution of craniofacial patterning is mediated by eye‐dependent and ‐independent processes in the cavefish Astyanax

Abstract: We studied the development and evolution of craniofacial features in the teleost fish, Astyanax mexicanus. This species has an eyed surface dwelling form (surface fish) and many different cave dwelling forms (cavefish) with various degrees of reduced eyes and pigmentation. The craniofacial features we examined are the tooth-bearing maxillary bones, the nasal and antorbital bones, the circumorbital bones, and the opercular bones, all of which show evolutionary modifications in different cavefish populations. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(200 citation statements)
references
References 21 publications
8
189
3
Order By: Relevance
“…It is currently unclear whether the RPE of teleosts induces scleral cartilage development. However, given that the scleral cartilage element is restricted to the equatorial region, that the lens influences scleral cartilage ossification (discussed below; Yamamoto et al, 2003) and that some aspects of eye development (i.e., the lens) differs between tetrapods and teleosts (Glass and Dahm, 2004;Cvekl and Tamm, 2004), it is possible that a different inductive mechanism exists in teleosts. What is needed is to determine whether the onset of scleral cartilage formation coincides with RPE differentiation and when the RPE obtains its ability to induce cartilage.…”
Section: Scleral Cartilage Development In Gallusmentioning
confidence: 99%
See 2 more Smart Citations
“…It is currently unclear whether the RPE of teleosts induces scleral cartilage development. However, given that the scleral cartilage element is restricted to the equatorial region, that the lens influences scleral cartilage ossification (discussed below; Yamamoto et al, 2003) and that some aspects of eye development (i.e., the lens) differs between tetrapods and teleosts (Glass and Dahm, 2004;Cvekl and Tamm, 2004), it is possible that a different inductive mechanism exists in teleosts. What is needed is to determine whether the onset of scleral cartilage formation coincides with RPE differentiation and when the RPE obtains its ability to induce cartilage.…”
Section: Scleral Cartilage Development In Gallusmentioning
confidence: 99%
“…Although teleosts are used currently as model organisms to study eye development (e.g., Yamamoto and Jeffery, 2002;Vihtelic and Hyde, 2002;Glass and Dahm, 2004), very few have specifically investigated eye development together with the surrounding skeletal element by means of direct larval manipulation. The most recent work is by Jeffery, Yamamoto, and colleagues in Astyanax mexicanus, the Mexican tetra (Yamamoto et al, 2003). This species exists as two morphs-a sighted surface form and a blind cavefish form in which the lens undergoes apoptosis shortly after its development.…”
Section: Development Of the Scleral Skeletal Elements In Teleostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurements of the size of the olfactory pits have shown that eyeless cavefish have a wider olfactory pit than eyed surface fish. The width of the olfactory pit is on average 12.9% larger due to the eyedependent developmental processes (Yamamoto et al 2003;Hinaux et al 2016). An enlarged olfactory pit could result in an enhanced sense of smell, which could directly correlate with the feeding skills of eyeless fish (Bibliowicz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The results are appearing from a number of contemporary laboratories, including (in hardly an exhaustive list) studies of ascidians (Jeffery et al,'99), amphioxus (Holland, 2002), hemichordates (Takacs et al, 2002;Lowe et al, 2003), a swarm of arthropods (Hughes and Kaufman, 2002), nematodes (Sommer, 2000), fish (Parichy and Johnson, 2001;Yamamoto et al, 2003), frogs (Callery et al, 2001), snakes (Cohn and Tickle, '99), starfish (Hart et al,'97), and sea urchins (Raff, '96;Wray, 2000). All of these systems offer particular advantages in addressing specific problems in the evolution of development, such as the role of Hox genes in the evolution of body form.…”
Section: Old Problems New Tools: the Evolutionary Developmental Biolmentioning
confidence: 99%